Appendix-derived Pseudomyxoma Peritonei (PMP): Molecular Profiling Toward Treatment of a Rare Malignancy. (August 2018) - Gleeson, Elizabeth M.; Feldman, Rebecca; Mapow, Beth L.; Mackovick, Lynn T.; Ward, Kristine M.; Morano, William F.; Rubin, Rene R.; Bowne, Wilbur B.
Abstract : Objectives: Pseudomyxoma peritonei (PMP) is a rare malignancy originating from the appendix, characterized by disseminated mucinous tumor implants on peritoneal surfaces. We examined the role of multiplatform molecular profiling to study biomarker-guided treatment strategies for this rare malignancy. Methods: A total of 54 patients with appendix-derived PMP were included in the study. Tests included one or more of the following: gene sequencing (Sanger or next generation sequencing), protein expression (immunohistochemistry), and gene amplification (C/fluorescent in situ hybridization). Results: Targeted sequencing of 47 genes detected variants in KRAS (81%), GNAS (74%), SMAD4 (16%), and ATM (16%). Mutations were found at low frequencies (n=1 to 2) in APC, BRAF, PIK3CA, MLH1, and TP53. GNAS and KRAS co-occurrence was found in 87%. Protein overexpression was found in epidermal growth factor receptor (83%), cyclooxygenase-2 (73%), cMET (63%), cKIT (58%), and platelet-derived growth factor receptor alpha (58%). Immune checkpoint expression was found in 36% (programmed cell death protein 1) and 18% (programmed death-ligand 1). Surrogate markers of cell proliferation were found at low rates (TLE3 23%, TOP2A 22%), consistent with the slow-growing biology of PMP. Phosophatase and tensin homolog was intact (wild type [100%]) and positive (immunohistochemistry [80%]). Patients exhibited stable microsatellite status and mismatch repair proficiency (93%). Importantly, multidrug resistance protein expression was elevated (100% BCRP, 94% MRP1, 88% PGP). Markers for gemcitabine (RRM1), fluorouracil (TS), oxaliplatin (ERCC1), and irinotecan (TOPO1) chemosensitivities were detected at favorable rates: 93%, 87%, 77% and 65%, respectively. Conclusions: Molecular profiling by multiple platforms identified potential therapies for the nontargetable KRAS-mutated population. The role of cMET-targeted therapeutics and immune checkpoint inhibitors merits further investigation. Biomarker-guided selection of cytotoxic chemotherapies may facilitate efficacy to systemic treatment.